Accelerated aging effects on seed vigour and plant performances in mungbean (vigna radiata l.) - Chan, Su Yi (2020)
Research on accelerated aging effects on seed vigour and plant performances in mungbean (Vigna radiata L.) was undertaken at Universiti Malaysia Sabah, Sandakan Campus. The research was divided into four studies: Study I: Evaluation of Initial Mungbean Seed Quality, Study II: Effect of Accelerated Aging on Mungbean Seed Quality, Study III: Effect of Seed Vigour on Mungbean Growth and Yield Traits, and Study IV: Relationship Between Quality Traits and Field Performance in Mungbean Seeds of Different Vigour. The initial standard germination and seedling vigour index of those seeds were recorded as 95 % and 19.68, respectively. This indicated that those seeds were highly viable and vigorous. The seeds were then subjected to accelerated aging treatments in order to obtain seedlots of varying vigour levels. They were exposed to high temperatures (41, 43 and 45oC), high relative humidity (≈95%) for 48 and 96 hours. The aging treatments were found to have significantly deleterious effects on mungbean seed quality. The extent of deterioration corresponded linearly with temperature and duration of aging. The higher the temperature and the longer the aging duration, the more severe was the damage. The resultant seedlots ranged in germination percentage from 95 % (for non-aged seeds) to 59.5 % (for those aged at 45oC for 96 hours) and their corresponding vigour indices dropped from 19.68 to 5.73. The different vigour seedlots obtained were evaluated for quality attributes in the laboratory as well as in the field. Quality traits evaluated in the laboratory included seed moisture content, seed leachate conductivity, germination percentage, germination index, seedling vigour index, length, fresh weight and dry weight of radicle and plumule. Laboratory evaluations revealed that all the seed quality attributes corresponded directly with their respective vigour levels, with the differences being significant. Tetrazolium test was rather hard to distinctly separate the variations in germination potential among the seedlots. Field evaluations included days to first emergence, field emergence percentage, plant height, days to first flowering, number of fruit clusters per plant, single pod length and weight, number of seeds per pod, 100-seed weight and seed yield per plant. Data revealed that all the yield components were significantly influenced by seed vigour, except days to first emergence, plant height and days to first flowering. Plants derived from the highest vigour seeds produced a seed yield of 35.37 g per plant while the lowest vigour seeds only produced 7.83 g of seed yield per plant. These findings proved that there was a relationship between quality traits and mungbean plant performances. Correlation of seed vigour and field performance become more remarkable as the differences in seed quality increase. Both laboratory and field experiments demonstrated that high vigour seeds outperformed low vigour seeds in almost all traits evaluated. Therefore, it is concluded that planting high vigour seeds can help to ensure success in crop establishment and productivity.